Dam Break Simulation of Sindangheula Dam Using HEC-RAS 2D - Angel Laurent Aldamike Dipra Sintia; Firyaal Nabila; Subekti Subekti; Bambang Adhi Priyambodho; Ngakan Putu Purnaditya; Bayu Krisna Wisnulingga (JURUSAN TEKNIK SIPIL, 2026)
Dams serve various utilities but inherently carry significant risks, particularly the potential for dam failure, which can lead to catastrophic flooding due to the sudden release of high-velocity flows toward downstream areas. While dam break simulations have been widely studied, no prior research has specifically analyzed the Sindangheula Dam using the HEC-RAS model. This study aims to simulate dam failure to determine the design flood discharges for Q1000 and QPMF, the resulting hydrographs following the dam break, and the extent of flood inundation. The design flood hydrographs in this simulation were generated using the Snyder method and modeled through the HEC-HMS software. The dam break analysis for Sindangheula Dam was conducted using a fully 2D model in HEC-RAS, incorporating both overtopping and piping failure scenarios Froehlich 2008. The hydrologic analysis yielded a Q1000 discharge of 498,27 m³/s and a QPMF discharge of 701,88 m³/s. The overtopping scenario produced the most severe impacts, with peak hydrographs reaching 5168,57 m³/s for Q1000 and 5267,21 m³/s for QPMF. Flood depths reached up to 18,27 m with an inundation area of 66,62 km² under Q1000, and up to 18,22 m with 70,44 km² under QPMF, submerging downstream regions including Taktakan, Serang, Cipocok, Kasemen, and Pontang.